The Effect of Hemiscorpius lepturus (Scorpionida: Hemiscorpiidae) Venom on Leukocytes and the Leukocyte Subgroups in Peripheral Blood of Rat - Mehri Ghafourian; Neda Ganjalikhanhakemi; Ali Asghar Hemmati; Rouhullah Dehghani; Wesam Kooti (Tehran University of Medical Sciences, 2016)
Background: The aim of this study was to investigate the effect of Hemiscorpius lepturus venom on leukocytes and the leukocyte subgroups in peripheral blood of rat. Methods: In this experimental study, sixty N-Mari rats were divided into three groups of 20 rats. Then the rats in each group were divided into four subgroups based on the blood sampling time that was 2, 6, 24 and 48 hours after the venom injection, respectively. The control group did not receive anything, however, the first and the second experimental groups received 0.1 and 0.01mg/kg of venom, subcutaneously. In accordance with a designated four sampling times, the blood sampling was carried out in three groups. After RBC lysis, the leukocytes and leukocyte subpopulations were determined and counted using appropriate hematological standard methods. Results: The leukocyte and the neutrophil count at two (P<0.05), six (P<0.01) and 24 (P<0.05) hours after the venom injection showed a significant decline compared with the control group, this decrease was significant at the dose of 0.1 mg/kg until 48 hours after the venom injection (P<0.05). The lymphocyte count showed a significant decline throughout the all hours of the experiment, compared with the control group (P<0.05). Conclusion: Leukocytes are probably affected by the cytotoxicity effect of the H. lepturus venom in a dose-dependent manner. This could be a wakeup call for the medical staff to perform quick and accurate treatment in the least time possible.